2017
DOI: 10.1007/s11356-017-9665-2
|View full text |Cite
|
Sign up to set email alerts
|

Nickel stressed responses of rice in Ni subcellular distribution, antioxidant production, and osmolyte accumulation

Abstract: Nickel has been found a key pollutant in farmlands of central and south China, and understanding of Ni toxicity in rice is of great significance in safety production of rice and remediation of Ni polluted paddy soils. The present study aimed to investigate the uptake and subcellular distribution of Ni, antioxidant production, and osmolyte accumulation of rice (Oryza sativa L., cv. yangliangyou 6) plants exposed to excessive Ni concentrations to gain an insight into Ni-induced phytotoxicity. Results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 62 publications
2
39
0
1
Order By: Relevance
“…Generally, ROS induced in the plant as a result of reaction among fatty acid and heavy metal (Shah et al 2001). The H 2 O 2 is an important component of ROS, and maximum produced when plants interact with heavy metals (Rizwan et al 2017). Our findings illustrated that H 2 O 2 production in rice seedlings was higher in response to increase the V concentration but the highest H 2 O 2 production was noted at 70 V mg L āˆ’1 .…”
Section: Influence Of V On Protein Contents and Its Accumulation In Rmentioning
confidence: 56%
“…Generally, ROS induced in the plant as a result of reaction among fatty acid and heavy metal (Shah et al 2001). The H 2 O 2 is an important component of ROS, and maximum produced when plants interact with heavy metals (Rizwan et al 2017). Our findings illustrated that H 2 O 2 production in rice seedlings was higher in response to increase the V concentration but the highest H 2 O 2 production was noted at 70 V mg L āˆ’1 .…”
Section: Influence Of V On Protein Contents and Its Accumulation In Rmentioning
confidence: 56%
“…Following cationic exchange for metals via the functional groups, alteration of lignin, cellulose and protein structural moieties leads to changes in the plantā€™s growth pattern, photosynthetic activity and antioxidant system 24,57 . Indeed, several studies reported single and combined effects of these metals (Cd, Cr, Cu, Ni and Pb) 58ā€“61 on photosynthetic activity, proline content and soluble sugars. Others are increased activities of total glutathione, ascorbate, peroxidase, superoxide dismutase and catalase in plant species including B. juncea, K. obovata, O. sativa, S. drummondii .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid industrialization is one of the main causes of environmental pollution, caused by the release of significantly large amounts of toxic metals, including nickel (Ni) (Rizwan et al, 2017). Ni is released into the environment from various anthropogenic activities, including metal mining and smelting, the burning of fossil fuels, vehicle emissions, the disposal of household and industrial wastes, and the application of fertilizers (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ni is released into the environment from various anthropogenic activities, including metal mining and smelting, the burning of fossil fuels, vehicle emissions, the disposal of household and industrial wastes, and the application of fertilizers (Chen et al, 2009). The amount of Ni in normal soils ranges from 10 to 1,000 mg kg āˆ’1 , but in high concentrations can cause substantial toxic effects on plants, including the inhibition of seed germination, reduction in plant growth and yield (Shukla & Gopal, 2009), induction of leaf chlorosis, necrosis, and wilting (Mosa et al, 2016), and peroxidation of lipids (Rizwan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%